2021
DOI: 10.1371/journal.pone.0248228
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of abortion among youth 15–24 in Ethiopia: A multilevel analysis based on EDHS 2016

Abstract: Introduction Determinants of the magnitude of abortion among women of diverse social and economic status, particularly in Africa poorly understood because of the missing information in most countries. In this study, we addressed abortion and its determinants among youth women of 15–24 ages to provide clear direction for policymaking in Ethiopia. Methods We examined the 2016 Ethiopian demographic health survey data downloaded from the EDHS website after obtaining permission on abortion among 15–24 age women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The objective of this study was to examine the pooled prevalence and factors that affect pregnancy termination in 12 East African countries from 2008 to 2018 using data from recent Demographic and Health Surveys. The pooled prevalence of pregnancy termination in East African countries was 7.79% [95% CI: 7.54, 8.04] with the highest pregnancy termination in Uganda 12.51% [95% CI: 11.56, 13.41] and the lowest pregnancy termination was observed in Ethiopia 5.26% [95% CI: 4.39, 6.16].The finding was significantly greater than previous studies in Ethiopia (2.5%) [ 24 ], Nigeria (5.8%) [ 27 ], Sub-Saharan Africa (5%) [ 28 ]. This finding was lower than studies in Democratic Republic of Congo [ 29 ], Gabon (34%) [ 30 ], and Cote D’lvoire (16.1%) [ 30 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The objective of this study was to examine the pooled prevalence and factors that affect pregnancy termination in 12 East African countries from 2008 to 2018 using data from recent Demographic and Health Surveys. The pooled prevalence of pregnancy termination in East African countries was 7.79% [95% CI: 7.54, 8.04] with the highest pregnancy termination in Uganda 12.51% [95% CI: 11.56, 13.41] and the lowest pregnancy termination was observed in Ethiopia 5.26% [95% CI: 4.39, 6.16].The finding was significantly greater than previous studies in Ethiopia (2.5%) [ 24 ], Nigeria (5.8%) [ 27 ], Sub-Saharan Africa (5%) [ 28 ]. This finding was lower than studies in Democratic Republic of Congo [ 29 ], Gabon (34%) [ 30 ], and Cote D’lvoire (16.1%) [ 30 ].…”
Section: Discussionmentioning
confidence: 72%
“…In Africa, unsafe abortion caused at least 9% of maternal deaths (or 16,000 deaths) in 2014 [ 10 ]. Previous studies revealed that maternal age [ 11 , 12 ], parity [ 13 , 14 ], occupation [ 15 ], age at first sex [ 13 , 16 ], marital status[ 17 , 18 ], place of residence [ 15 ], Media exposure [ 19 ], wealth index [ 15 , 20 ], education status [ 21 , 22 ] and region [ 23 , 24 ] were significantly associated factor with pregnancy termination.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, previous studies on pregnancy termination among AGYW have identified socio-demographic factors such as age, ethnicity, parity, occupation, age at first sex, marital status, place of residence, and region as factors associated with pregnancy termination among AGYW [8][9][10]. These studies were done in countries with lower fertility rates compared to countries, which have higher fertility rates [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Ethiopian context also supports the importance of distance to church/mosque in affecting religious activities, such as frequency of attendance to prayers and religious education. While most Ethiopians report the importance of religion (Gilano & Hailegebreal, 2021) and their daily life is linked to religious activities (Chaillot, 2002), our key informant interview with religious leaders indicate that the frequency of attendance to prayers and religious education (evening and Sunday schools), adherence to religious moral and commitment to the commandments is likely to be higher among members of households located closer to churches/mosques. When it comes to our sample of households, all belong to one of the three Christianity denominations (Orthodox (85.47%), Protestant (.24%) and Catholic (.61%) or Islam (13.68%).…”
Section: Econometric Methods and Identificationmentioning
confidence: 82%